The Effectiveness Of Death Execution On Narcotics Crime As Law Enforcement - Tithos Briyan Pamungkas Sumanang; Amin Purnawan (Universitas Islam Sultan Agung, 2021)
This study aims to review the Narcotics Law that applies in Indonesia, especially Act No. 35 of 2009 concerning Narcotics. In addition, this research is also expected to find out the obstacles and solutions in law enforcement efforts against narcotics criminals. The research approach method that will be used in the research is the juridical-sociological method. From the results of this study, it is concluded that theoretically the applicable narcotics law has been very effective in investigating narcotics criminals, and in practice the law is also very helpful in completing investigations against narcotics criminals in Indonesia and the execution of the death penalty is one of the hard law enforcement efforts to emphasize that narcotics abuse is a very dangerous thing. However, the problem of narcotics abuse is not only a national problem, it has become an international problem that cannot be solved only with existing regulations, professionals from law enforcement officials are also very much needed in cracking down on narcotics abuse, and the role of public awareness is also important, in order to stay away from narcotics abuse.